Traders - Mark Fenton-O'Creevy (Oxford University Press, 2005)
This is a book about traders in financial markets: what they do, the kind of people they are, how they perceive the world they inhabit, how they make decisions and take risks. This is also a book about how traders are managed--the best and the worst examples--and about the institutions they inhabit: firms, markets, cultures, and theories of how the world works. How these institutions function, how traders are managed, and how traders view the world, all have profound effects on the wider financial environment. This book explores these relationships and their implications theoretically and empirically